Global Economic Prospects, January 2016 : Spillovers Amid Weak Growth - World Bank Group (Washington, DC: World Bank, 2015)
The January 2016 edition of Global Economic Prospects discusses current global and regional economic developments and prospects, analyzing key challenges and opportunities confronting developing countries. This volume addresses, among other topics, spillovers from large emerging markets and macroeconomic vulnerabilities during resource development.